Risk Factors Associated with Severe Pre-Eclampsia - Liliek Pratiwi (Indonesian Journal of Nursing and Health Sciences, 2025)
PEB (severe pre-eclampsia) is influenced by several variables, including maternal age during pregnancy, parity, gestational age, number of fetuses, frequency of antenatal care (ANC) appointments, and any history of hypertension. Identifying these elements among particular groups helps to direct successful therapeutic interventions and inform public health policies. This study was designed as a case-control study and used analytic observational techniques. Date were collectedfrom the medical records of women giving birth and without preeclampsia at the obstetrics and gynecology departement of Dr. Slamet General Hospital in Garut. The results of bivariate analysis using the chi-square test showed that there was no significant relationship between risk factors, including maternal age, parity, gestational age, number of fetuses, and ANC visits, with p-values greater than 0.05. based on multivariate analysis using logistic regression testing, it was found that pregnant women over the age of 35 had a higher risk of developing severe preeclampsia, with a significance value of p = 0.034. these findings indicate that maternal age over 35 and a history of hypertension play a role in increasing the likelihood of PEB.